2005
DOI: 10.1016/j.eupc.2005.08.242
|View full text |Cite
|
Sign up to set email alerts
|

Severe Left Ventricular Systolic Dysfunction Increases Atrial Fibrillation After Ablation of Atrial Flutter

Abstract: A 58 year old female underwent orthotopic left lung transplantation for emphysema. She enjoyed rapid recovery from her surgical procedure but developed almost daily episodes of symptomatic palpitations, persisting 32 months following transplant.Electrocardiogram demonstrated atypical atrial flutter, and she reported to the electrophysiology (EP) laboratory for mapping and catheter ablation.At EP study, she was found to have left atrial flutter, cycle length 230 ms, with variable atrioventricular conduction. En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In four studies of highly selected patients with HF/ left ventricular systolic dysfunction (LVSD) and AFL referred for ablation, 33% overall (range 25% to 57%) had concurrent AF ( Table 2 ). 22 , 43 , 44 , 61 Following AFL ablation, AF developed in 17–30% of patients over 350 days to 2 years. 22 , 61 De novo AF was strongly associated with LVSD following AFL ablation:: 43% vs. 14% comparing LVEF < 50% vs. >50%, and 31% vs. 7% for LVEF < 35% vs. 36–55% in two US single‐centre cohorts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In four studies of highly selected patients with HF/ left ventricular systolic dysfunction (LVSD) and AFL referred for ablation, 33% overall (range 25% to 57%) had concurrent AF ( Table 2 ). 22 , 43 , 44 , 61 Following AFL ablation, AF developed in 17–30% of patients over 350 days to 2 years. 22 , 61 De novo AF was strongly associated with LVSD following AFL ablation:: 43% vs. 14% comparing LVEF < 50% vs. >50%, and 31% vs. 7% for LVEF < 35% vs. 36–55% in two US single‐centre cohorts.…”
Section: Resultsmentioning
confidence: 99%
“… 22 , 43 , 44 , 61 Following AFL ablation, AF developed in 17–30% of patients over 350 days to 2 years. 22 , 61 De novo AF was strongly associated with LVSD following AFL ablation:: 43% vs. 14% comparing LVEF < 50% vs. >50%, and 31% vs. 7% for LVEF < 35% vs. 36–55% in two US single‐centre cohorts. 22 , 61 In the remaining cohort and case series studying tachycardia‐induced cardiomyopathy, the small sample sizes limit meaningful conclusions regarding the overlap.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ideally, patients with a higher baseline risk for developing newly diagnosed AF after cAFL ablation should be identified by risk factors, in order to direct resources for a more intense follow-up of these patients. Although some prior studies have identified such risk factors, including age [ 13 ], left ventricular dysfunction [ 1 , 14 , 15 ], left atrial dilatation [ 2 , 16 ] and arterial hypertension [ 1 ], these were not consistent across studies [ 17 ]. In our study, we only identified coronary artery disease as a significant predictor for recurrent AF or AT.…”
Section: Discussionmentioning
confidence: 99%